(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2019)
Crimean Congo hemorrhagic fever (CCHF) is a zoonotic disease. It is caused by an RNA virus in wild and domestic mammals, birds and ticks. It is the family of Bunyaviridae from the Arbovirus group. The main vector and reservoir of the CCHF virus are hard-body ticks principally of the Hyalommagenus. The Hyalomma tick bite infection has the highest rate of nosocomial transmission especially due to direct human to human contact. India reported its first CCHF case in the year 2011 from Ahmadabad, Gujarat. Since then, several sporadic cases and outbreaks of CCHF have been reported the most from Gujarat and few from Rajasthan and the Uttar Pradesh States of India. Animals do not show clinical signs but may act as a source of infection for humans. The virus is transmitted from animals to humans either by direct contact with the blood or tissue of infected animals. Laboratory tests used to diagnose CCHF include reverse transcriptase (RT)-PCR, immunofluorescence assay (IFA), antibody (IgG, IgM) and antigen-capture ELISA, and isolation of the virus. Ribavirin acts as an effective anti-viral agent against CCHFV by inhibiting its replication. Supportive therapy including the administration of erythrocytes, thrombocytes, and fresh frozen plasma acts as an important strategy to control CCHF at an early stage.